Analysis of Language Errors in Product Marketing on Facebook Market Place - La Ode Muhammad Idrus Hamid Basri; Miftah-ul Khaira Anwar; Muhammad Kamal Bin Abdul Hakeem (Lingeduca: Journal of Language and Education Studies, 2024)
This research aims to identify language errors that occur in product marketing on Facebook Marketplace with a focus on the morphological level. The research method used is descriptive analysis with a content analysis approach. The research results show that, apart from the problem of abbreviations, spelling errors are also a major concern. Some marketplace accounts tend to make mistakes in letter placement or word writing, which can result in unclear messages being conveyed. This kind of error can change the meaning of a sentence and make it difficult for consumers to understand the information provided. These findings provide important insights for marketing practitioners in improving the quality of their communications on the Facebook Marketplace platform.